Comparative Assessment of Phenolic Compounds from Authentic Wine Varieties from North-Western Romania from the 2021-2022 Harvest - Bogdan Florin HODIȘAN; Floricuța RANGA; Elena-Suzana BIRIȘ-DORHOI; Anca-Corina FĂRCAȘ; Maria TOFANĂ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2023)
Wine is one of the most consumed beverages in the world. Romania, as a country, has a history in vineyards and wine making. This present study analyzed the phenolic compounds of 5 varieties of wine from Romania (Fetească Regală Muscat Ottonel, Riesling Italian, Pinot Gris and Merlot). The results suggested that some of the wines present a wide category of phenolic compounds where others present low values and some of the compounds are absent as detected with a developed HPLC-DAD-ESI+ method. Phenolic compounds were identified after the retention time. Merlot wine presented, in most cases, the highest values for phenolic compounds, with a few exceptions. As a conclusion, romanian wines are rich in phenolic compounds that possess a series of beneficial properties.